2005
DOI: 10.1177/0091270005279636
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics of Anthocyanins and Ellagic Acid in Healthy Volunteers Fed Freeze‐Dried Black Raspberries Daily for 7 Days

Abstract: Eleven subjects completed a clinical trial to determine the safety/tolerability of freeze-dried black raspberries (BRB) and to measure, in plasma and urine, specific anthocyanins-cyanidin-3-glucoside, cyanidin-3-sambubioside, cyanidin-3-rutinoside, and cyanidin-3-xylosylrutinoside, as well as ellagic acid. Subjects were fed 45 g of freeze-dried BRB daily for 7 days. Blood samples were collected predose on days 1 and 7 and at 10 time points postdose. Urine was collected for 12 hours predose on days 1 and 7 and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
108
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 140 publications
(112 citation statements)
references
References 24 publications
3
108
1
Order By: Relevance
“…On the basis of their chemical composition as well as strongly supportive preclinical in-vitro and in-vivo data generated by our laboratories, FBR was selected as the bioactive constituents to incorporate into these gels (9-13). Essential for human applications, our Phase I clinical trial demonstrated that consumption of large quantities of FBR are well tolerated in humans (14). A final consideration is the pharmacologic benefit derived from local delivery formulations; specifically the ability to obtain therapeutically relevant local levels without development of systemic complications.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…On the basis of their chemical composition as well as strongly supportive preclinical in-vitro and in-vivo data generated by our laboratories, FBR was selected as the bioactive constituents to incorporate into these gels (9-13). Essential for human applications, our Phase I clinical trial demonstrated that consumption of large quantities of FBR are well tolerated in humans (14). A final consideration is the pharmacologic benefit derived from local delivery formulations; specifically the ability to obtain therapeutically relevant local levels without development of systemic complications.…”
Section: Discussionmentioning
confidence: 99%
“…The berries were harvested mechanically (with a picker) in a total period of 4 hr, washed, and frozen at −20°C within an hour of the time of harvest. The berries remain frozen until they are transported frozen to Van Drunen Farms in Momence, IL, where they are then freeze-dried and ground into a powder as described previously (9)(10)(11)(12)(13)(14).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…A trial with eleven subjects was undertaken to determine the safety/tolerability of freeze-dried BRBs and to measure anthocyanins and ellagic acid in the plasma and urine [49] in subjects fed 45 grams (equivalent to a 5% BRB diet in animals) of freeze-dried BRB powder as a slurry in water daily for 7 days. Blood samples were collected predose on days 1 and 7 and at 10 time points over a period of 12 hours postdose.…”
Section: Toxicitymentioning
confidence: 99%
“…6 The research has shown that acylated ACNs may behave quite differently from their nonacylated counterparts, in terms of their stability and bioavailability; (Stoner et al, 2005), hence it is not reasonable to consider all ACNs equally. Therefore, knowledge regarding the concentrations and daily intake of specific ACNs is essential.…”
Section: Introductionmentioning
confidence: 99%